Determining the relationship between fanpage contents and PTA metrics - Rahman, Zoha; Zanuddin, Hasmah; Suberamanian, Kumaran; Moghavvemi, Sedigheh; Md Nasir, Mohd Hairul Nizam (2016)
Social Media is now determined as an excellent communicative tool to connect directly with consumers. One of the most significant ways to connect with the consumers through these Social Networking Sites (SNS) is to create a facebook fanpage with brand contents and to place different posts periodically on these fanpages. According to different posts or contents placed on the fanpages, consumer responses in different ways. Usually users become fans of particular brand fanpages or put like, comments or keep sharing on particular posts of fanpages. These types of consumer activities in fanpages reflect brands' post popularity. Most importantly, in measuring social networking sites' effectiveness, corporate houses are now analyzing metrics in terms of calculating engagement rate, number of comments/share and likings in fanpages. So now, it is very important for the marketers to know the effectiveness of different contents or posts of fanpages in order to increase the fan responsiveness and engagement rate in the fan pages. In the study the authors have analyzed total 1325 brand posts from 14 international brands of Electronics companies. Data of 9 months (From December 2014- August 2015) have been collected for analyses, which are available online from Brand' fan pages. Study explored the impact of contents (most frequently posted contents) on the user actions or PTA (People Talking About) metrics. Cross section Data Regression analysis was conducted by EVIEWS 9 software to analyze the non-parametric data.